Correlation Cycle Threshold (Ct) values and clinical symptoms of pediatric patients with COVID-19 - Hutabarat, Andrew Partogi Hamonangan; Hutabarat, Sabar; Aurora, Wahyu Inda Dewi (Medical Faculty of Brawijaya University, Indonesia, 2024)
Introduction: The COVID-19 pandemic has affected individuals of all age groups, including children. Understanding the correlation between cycle threshold values and clinical symptoms in pediatric patients with COVID-19 is crucial for accurate diagnosis and management of the disease. This research aims to determine the correlation of Cycle Threshold (CT) Values with Clinical Symptoms Of Pediatric Patients With COVID-19. Methods: This research uses quantitative design with a cross sectional study approach. The population in this study was all children diagnosed with COVID-19 at hospitals in Jambi City in 2021. The data for this study were collected by reviewing the medical records of children registered at Jambi City Hospital who were diagnosed with confirmed cases of COVID-19. Data analysis of this study used univariate and bivariate analysis. Result: From the characteristics of respondents, it was found that the majority of respondents were aged 11-18 years (58%) and male (58%). From the distribution of clinical symptoms, it was found that some receptors had milder symptoms (48%). The results of this study show that clinical symptoms are significantly associated with low CT values in pediatric patients with COVID-19 (p = 0.000). Conclusion: CT values show a positive correlation with clinical symptoms in pediatric patients with COVID-19. A rising Ct value might suggest a declining viral load, potentially indicating recovery.